Sultan Bahu’s Poetry: A Sociological Analysis of Sufi Poems - Naich, Moula Bux; Sahito, Muhammad Shahban; Qureshi, Aleena (Annals of Human and Social Sciences, 2023)
This study explores the themes of divine love, spiritual awakening, and the human experience in Sultan Bahu’s poetry. The research seeks to shed light on the mystical teachings and philosophical insights revealed in his works by closely examining his lyrics. A contemporary perspective on Sultan Bahu’s mystic poetry by acknowledging several narratives of thinking. Define metaphor, identity, value, ideology, belief, and appraisal. The study is qualitative in nature, using the purposive sampling technique to choose various passages from Bahu’s poetry. The study aims to provide a comprehensive analysis of Sultan Bahu’s mystic poetry by examining these themes. Results of this study show that Bahu preaches Allah’s (God’s) holy message to his people using varied metaphors derived from his surroundings. By studying his poetry, readers can gain insight into the divine wisdom and guidance that Bahu sought to impart to his audience. It allows us to connect more deeply with the spiritual messages and lessons he shared.